Nilai Tukar Rupiah terhadap Dollar AS Berpengaruh Signifikan terhadap Belanja Negara Indonesia, 1994-2008 - Rakhmat Priyono (EKO-REGIONAL, 2010)
This research is purposed to analyze the influence of economic growth, inflation, exchange rate, and the world oil price, partially and simultaneously, toward Indonesia Government Expenditur. The results show that by partially, economic growth, inflation, exchange rate, and the world oil price have a positive influence toward Indonesia Government Expenditure. By simultaneously, all of variable affect Indonesia Government Expenditure, while the most significant variable influencing the expenditure  is exchange rate. The implication of this research are: first, the government should make accurate, reliable, and correct assumption about the indicators of macro economic which are affected Indonesia Government Expenditure;  second, the government should maintain the stability of exchange rate. Keywords:economic growth, exchange rate, government expenditure,inflation